Waveform and packet structure of lion roars - W. Baumjohann; R. A. Treumann; E. Georgescu; E. Georgescu; G. Haerendel; K.-H. Fornacon; U. Auster (Annales Geophysicae, 1999)
The Equator-S magnetometer is very sensitive and has a sampling rate of normally 128 Hz. The high sampling rate allows for the first time fluxgate magnetometer measurements of ELF waves between the ion cyclotron and the lower hybrid frequencies in the equatorial dayside magnetosheath. The so-called lion roars, typically seen by the Equator-S magnetometer at the bottom of the magnetic troughs of magnetosheath mirror waves, are near-monochromatic packets of electron whistler waves lasting for a few wave cycles only, typically 0.25 s. They are right-hand circularly polarized waves with typical amplitudes of 0.5–1 nT at around one tenth of the electron gyrofrequency. The cone angle between wave vector and ambient field is usually smaller than 1.5°. Key words. Interplanetary physics (MHD waves and turbulence; plasma waves and turbulence)